Evaluation of growth performance of Brahman cross calves to local environment of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The present study was conducted using growth performance data on 624 Brahman cross (25%) calves collected from three villages adjacent to Bangladesh Agricultural University, Mymensingh, Bangladesh. Growth performance data of 289 Brahman cross (50%) calves were also collected from record sheet maintained at 12 Upazila Livestock Offices under the "Beef breed development project" of Department of Livestock Services to compare performance between 25% and 50% Brahman cross calves. Growth performance traits were considered birth weight, weight at three-, six-, nine-, twelve-month of age, average daily gain from birth to twelve-month of age. Calving difficulties (dystocia) and calf mortality were also included in the study area. The birth weight, weight at three-, six-, nine- and twelve-month average daily gain for 25% Brahman cross calves were 19.79±0.20, 52.72±1.31, 86.61±2.02, 129.90±3.08, 172.60±3.48 kg and 426.00±4.99g, respectively. The average birth weight (21.40±0.24 kg) and twelve-month weight (229.62±2.08 kg) of 50% Brahman cross calves were significantly higher (p